Diagnóstico del desarrollo socioeducativo asociado al proyecto de vida, en los estudiantes de Educación General Básica Media de la Unidad Educativa Sicalpa, cantón Colta, durante el año lectivo 2022-2023 - Gualli Orosco, Abigail Anahi (2024)
The purpose of this research was to carry out the diagnosis of the socio-educational development associated with the life project, in the Middle Basic Education students of the Sicalpa Educational Unit, during the 2022-2023 school year. With a qualitative approach, exploratory scope, diagnosis, non-experimental design. The population was made up of 42 students enrolled in Middle Basic Education. The survey was used as a data collection technique and the structured questionnaire as an instrument. Among the relevant results, in terms of socio-educational development, it stands out that students present weaknesses in teamwork, in fully complying with instructions and sharing their emotions with others. Regarding the life project, there is a significant majority that plans to pursue a university career, however, there is a minority of the population studied that has not thought about their future, they see their teachers as transmitters of knowledge, but they do not take them as guides for the life project. This study concludes that in the group studied there is a strong academic base, however, the emotional support for strengthening the personality that contributes to the achievement of the life project is weak.